Reconstruction of the human gastrocnemius force-length curve in vivo: Part 1—Model-based validation of method - Winter, S. L.; Challis, J. H. (Journal of Applied Biomechanics, 2008)
The muscle fiber force-length relationship has been explained in terms of the cross-bridge theory at the sarcomere level. In vivo, for a physiologically realistic range of joint motion, and therefore range of muscle fiber lengths, only part of the force-length curve may be used; that is, the section of the force-length curve expressed can vary. The purpose of this study was to assess the accuracy of a method for determining the expressed section of the force-length curve for biarticular muscles. A muscle model was used to simulate the triceps surae muscle group. Three model formulations were used so that the gastrocnemius operated over different portions of the force-length curve: the ascending limb, the plateau region, and the descending limb. Joint moment data were generated for a range of joint configurations and from this simulated data the region of the force- length relationship that the gastrocnemius muscle operated over was successfully reconstructed using the algorithm of Herzog and ter Keurs (1988a). Further simulations showed that the correct region of the force-length curve was accurately reconstructed even in the presence of random and systematic noise generated to reflect the effects of sampling errors, and incomplete muscle activation.